PENGARUH BUDAYA ORGANISASI, MOTIVASI DAN GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA - Restu Hayati, 08.05.51.0120; Abdul Rozak, Hasan (Students Journal of Economic and Management, 2012)
The study aims to examine and analyze the organizational culture efect. Work motivation and leadership styles on job satisfaction of employees in the study population is PT.Indofood Semarang employee who bejumlah 1737 people. Based on the calculation formula slovin samples in this study amounted to 94.5 rounded to 95 respondents. Techniques of data analysis in this study usingmultiple linear regression while hypothesis testing using t test and F test Based on survey results revealed that there are positive and significant influence of organizational culture (X1)on job satisfaction of employees (Y), there are positive and significant influence between motivation (X2) on job satisfaction laryawan (Y), there are positive and significant effect of style leadership (X3) on job satisfaction of employees (Y), organizational culture, motivation and leadership styles together have a positive and significant impact on employee job satisfaction.Based on the coefficient of determination there is the influence of motivational variables (X1), the variable of work discipline (X2), the work environment variables (X3) jointly affect the performance variable (Y) is 73.9% while the remaining amount of 26.1%. Key words: Culture organisasi, motivation, leadership style and job satisfaction.